1985
DOI: 10.1007/bf00421601
|View full text |Cite
|
Sign up to set email alerts
|

Switching genes in Schizosaccharomyces pombe

Abstract: In homothallic (h 90) Schizosaccharomyces pombe strains mutants occur which exhibit reduced frequencies of mating-type switching. The colonies of such mutants show a mottled iodine reaction. The underlying mutations map either in a switching signal at matl or in switching (swi) genes which are not linked to the mating-type region. Forty-nine swi mutants were examined. They map in ten different swi genes, swil to swil 0. Seven swi genes were assigned to chromosomes I and II, respectively. - Two classes of swi g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…As a result of a search by BLAST in the databases of the NCBI, the swi3 ORF showed high similarity in amino acid sequence with mammalian and mouse timeless-interacting protein (Tipin) (2e-09 and 8e-08, respectively). The swi3-146, swi3-157, and swi3-1 mutations, causing defects in mating type switching (22), were identified by direct sequencing of PCR-amplified mutant alleles from strains E146, E157, and SG381, respectively. The swi3-146, swi3-157, and swi3-1 mutations changed the third [G to A (M1I)] and the 259th nucleotides [C to T(ochre)] and inserted A after the 132nd nucleotide (frame shift) of the wild-type swi3 ORF, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of a search by BLAST in the databases of the NCBI, the swi3 ORF showed high similarity in amino acid sequence with mammalian and mouse timeless-interacting protein (Tipin) (2e-09 and 8e-08, respectively). The swi3-146, swi3-157, and swi3-1 mutations, causing defects in mating type switching (22), were identified by direct sequencing of PCR-amplified mutant alleles from strains E146, E157, and SG381, respectively. The swi3-146, swi3-157, and swi3-1 mutations changed the third [G to A (M1I)] and the 259th nucleotides [C to T(ochre)] and inserted A after the 132nd nucleotide (frame shift) of the wild-type swi3 ORF, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier research, genetic screening for mutations affecting both mating type switching and the level of double-strand break implicated swi1, swi3, and swi7 in the switching process (16,22). Doublestrand break has also been shown to efficiently initiate meiotic mat1 gene conversion (30).…”
mentioning
confidence: 99%
“…The primers used in these procedures are available on request. Mutations and epitopetagged genes have previously been described for cdc25-22 (Fantes 1979), swi1D (swi1TKan r ) , swi3D (swi3TKan r ) (Noguchi et al 2004), swi3-1 (Gutz and Schmidt 1985), cds1D (cds1Tura4 1 ) (Boddy et al 1998) , swi1-GFP (swi1-GFP-Kan r ) , swi3-GFP (swi3-GFPKan r ) (Noguchi et al 2004), swi1-3FLAG (swi1-3FLAG-Kan r ) (Noguchi et al 2004), uve1D (uve1TLEU2) (Yonemasu et al 1997), rad13D (rad13Tura4 1 ) (Yonemasuet al 1997), and orp1-5FLAG (orp1-5FLAG-Kan r ) (Ogawa et al 1999).…”
Section: General Techniquesmentioning
confidence: 99%
“…By 20.2% identity in a region of 104 amino acids. Rad5O is required for recombination (mitotic and meiotic) and for DSB DNA repair during vegetative growth in S. cerevisiae (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…The first class is composed of three trans-acting switch (swi) loci (swil, swi3, and swi7), which are required for producing a high level of DSB (6,14,20). We have recently shown that swi7 encodes the catalytic subunit of DNA polymerase a (45).…”
mentioning
confidence: 99%